Envy and Compassion in Tournaments - Christian Grund; Dirk Sliwka (Institute for the Study of Labor (IZA), 2002)
Many experiments indicate that most individuals are not purely motivated by material self interest, but also care about the well being of others. In this paper we examine tournaments among inequity averse agents, who dislike disadvantageous inequity (envy) and advantageous inequity (compassion). It turns out that inequity averse agents exert higher effort levels than purely self-interested agents for a given prize structure. Contrary to standard tournament theory first-best efforts can not be implemented when prizes are endogenous. Several extensions are studied like the case of spiteful agents, sabotage, asymmetric agents and an application on the choice between vertical and lateral promotions within firms.
Keywords: D63; D23; M52; M51; 330; tournaments; promotions; inequity aversion; Erwerbsverlauf; Wettbewerb; Spieltheorie; Leistungsmotivation; Gerechtigkeit; Theorie; Tournament; inequity aversion